Fenchone, a monoterpene: Toxicity and diuretic profiling in rats - Bashir, Asifa; Mushtaq, Muhammad Naveed; Younis, Waqas; Anjum, Irfan (Frontiers in Pharmacology, 2023)
Fenchone a monoterpene present in the essential oils of various plants including Foeniculum vulgare and Peumus boldus. Due to its antioxidant and various biological activities, this current research was designed to evaluate its diuretic activity along with its toxicity profiling. For evaluating acute toxicity, OECD guideline 425 was followed. A single dose of 2000mg/kg was orally administered to rats. For evaluating the diuretic potential, three doses of Fenchone (100,200 and 400mg/kg) were assayed in comparison to furosemide (15mg/kg) as standard drug in rats followed by measurement of urinary volume, urinary electrolytes, uric acid and urinary creatinine in saline loaded rats for 8 hrs. Acute toxicity study showed that significant increase in Hemoglobin (Hb) and Red blood cells (RBC’s), alkaline phosphatase (ALP) and alkaline transaminase (ALT) along with a significant decrease in serum triglycerides, cholesterol and uric acid levels when compared with control group. . The oxidative stress parameters superoxide dismutase (SOD) was increased in heart and spleen and nitrite (NO) level and Glutathione levels were decreased in kidney. The acute diuretic effect of Fenchone (400mg/kg) significantly increased the urinary output, electrolytes (Na+, K+ and Ca++), urinary creatinine and urinary uric acid in a dose-dependent manner and the results were in comparison to furosemide. The Na+/K+ ratio was remarkably increased in treatment group as compared to the control group. Diuretic index, Saluretic index and Lipschitz value was also calculated from electrolytes concentration and urinary volume measurements and the values were significantly increased in Fenchone at 400mg/kg dose level group. The current study concluded that fenchone is safe and has remarkable diuretic action.